Vom ‚Komaglotzen‘ zum literar- und medienästhetischen Lernen. Konzeptualisierung eines fernsehseriellen Lehr-Lern-Settings am Beispiel des Teen Dramas ANNE WITH AN E. - Kißling, Magdalena (Der Deutschunterrich (2))

La tragedia amorosa dell'"Adone" ossia il nuovo ordinamento dell’amore - Steigerwald, Jörn (L’“Adone“ di Giovan Battista Marino. Mito - Movimento - Maraviglia. Atti del convegno internazionale (Humboldt-Universität zu Berlin, 1-2 luglio 2019))

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas D (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

When water becomes an integral part of carbon – combining theory and experiment to understand the zeolite-like water adsorption properties of porous C2N materials - Heske, Julian Joachim; Walczak, Ralf; Epping, Jan D.; Youk, Sol; Sahoo, Sudhir K.; Antonietti, Markus; Kühne, Thomas; Oschatz, Martin (Journal of Materials Chemistry A)
The origin of strong interactions between water molecules and porous C 2 N surfaces is investigated by using a combination of model materials, volumetric physisorption measurements, solid-state NMR spectroscopy, and DFT calculations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Hydrogen bond dynamics of interfacial water molecules revealed from two-dimensional vibrational sum-frequency generation spectroscopy - Ojha, Deepak; Kühne, Thomas (Scientific Reports)
Abstract Vibrational sum-frequency generation (vSFG) spectroscopy allows the study of the structure and dynamics of interfacial systems. In the present work, we provide a simple recipe, based on a narrowband IR pump and broadband vSFG probe technique, to computationally obtain the two-dimensional vSFG spectrum of water molecules at the air–water interface. Using this technique, to study the time-dependent spectral evolution of hydrogen-bonded and free water molecules, we demonstrate that at the interface, the vibrational spectral dynamics of the free OH bond is faster than that of the bonded OH mode.
Keywords: Multidisciplinary

Organic Mixed-Valence Compounds and the Overhauser Effect in Insulating Solids - Pylaeva, Svetlana; Marx, Patrick; Singh, Gurjot; Kühne, Thomas; Roemelt, Michael; Elgabarty, Hossam (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Artificial Neural Networks as Trial Wave Functions for Quantum Monte Carlo - Kessler, Jan; Calcavecchia, Francesco; Kühne, Thomas (Advanced Theory and Simulations)
Keywords: Multidisciplinary; Modeling and Simulation; Numerical Analysis; Statistics and Probability

Artificial neural networks for the kinetic energy functional of non-interacting fermions - Ghasemi, Alireza; Kühne, Thomas (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

A combinatorial study of electrochemical anion intercalation into graphite - Chugh, Manjusha; Jain, Mitisha; Wang, Gang; Nia, Ali Shaygan; Mirhosseini, Hossein; Kühne, Thomas (Materials Research Express)
Abstract Dual-ion batteries are considered to be an emerging viable energy storage technology owing to their safety, high power capability, low cost, and scalability. Intercalation of anions into a graphite positive electrode provides high operating voltage and improved energy density to such dual-ion batteries. In this work, we have performed a combinatorial study of graphite intercalation compounds considering four anions, namely hexafluorophosphate (PF <?CDATA ${}_{6}^{-}$?> 6 − ), perchlorate (ClO <?CDATA ${}_{4}^{-}$?> 4 − ), bis(fluorosulfonyl)imide (FSI − ), and bis(trifluoromethanesulfonyl)imide (TFSI − ), via first-principles calculations. The structural properties and energetics of the intercalation compounds are compared based on different sizes, geometries, and the physical and chemical properties of the intercalated anions. The staging mechanism of anion intercalation into graphite and the specific capacities, and voltage profiles of the intercalated compounds are investigated. A comparison regarding battery electrochemistry is also done with available experimental observations. Our calculated intercalation energies and voltage profiles show that the initial anion intercalation into graphite is less favorable than subsequent ones for all the anions considered in this study. Although the effect of the size of anions in a graphite cathode on various properties of the intercalated compounds is not as significant as the size of cations in a graphite anode, some distinction between the studied anions can still be made. Among the studied anions, the intercalation compounds based on PF <?CDATA ${}_{6}^{-}$?> 6 − are the most stable ones. These PF <?CDATA ${}_{6}^{-}$?> 6 − anions cause relatively small structural deformations of the graphite and have the highest oxidative ability, highest onset voltage, and highest diffusion barrier along the graphene sheets. The overall small diffusion barriers of the anions within graphite explain the high rate capability of dual-ion batteries.
Keywords: Metals and Alloys; Polymers and Plastics; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Full Assignment of Ab-Initio Raman Spectra at Finite Temperatures Using Wannier Polarizabilities: Application to Cyclohexane Molecule in Gas Phase - Partovi-Azar, Pouya; Kühne, Thomas (Micromachines)
We demonstrate how to fully ascribe Raman peaks simulated using ab initio molecular dynamics to specific vibrations in the structure at finite temperatures by means of Wannier functions. Here, we adopt our newly introduced method for the simulation of the Raman spectra in which the total polarizability of the system is expressed as a sum over Wannier polarizabilities. The assignment is then based on the calculation of partial Raman activities arising from self- and/or cross-correlations between different types of Wannier functions in the system. Different types of Wannier functions can be distinguished based on their spatial spread. To demonstrate the predictive power of this approach, we applied it to the case of a cyclohexane molecule in the gas phase and were able to fully assign the simulated Raman peaks.
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Control and Systems Engineering

Photocatalytic Water Splitting Reaction Catalyzed by Ion-Exchanged Salts of Potassium Poly(heptazine imide) 2D Materials - Sahoo, Sudhir K.; Teixeira, Ivo F.; Naik, Aakash; Heske, Julian Joachim; Cruz, Daniel; Antonietti, Markus; Savateev, Aleksandr; Kühne, Thomas (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

Ultrafast solvent-to-solvent and solvent-to-solute energy transfer driven by single-cycle THz electric fields - Balos, Vasileios; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Netz, Roland; Bonthuis, Douwe Jan; Kaliannan, Naveen; Loche, Philip; Kampfrath, Tobias; Sajadi, Mohsen (Terahertz Emitters, Receivers, and Applications XII)

A theoretical investigation of topological phase modulation in carbide MXenes: Role of image potential states - Wang, Mengying; Ranjbar, Ahmad; Kühne, Thomas; Belosludov, Rodion V.; Kawazoe, Yoshiyuki; Liang, Yunye (Carbon)
Keywords: General Chemistry; General Materials Science

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; López-Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Influence of different ester side groups in polymers on the vapor phase infiltration with trimethyl aluminum - Mai, Lukas; Maniar, Dina; Zysk, Frederik; Schöbel, Judith; Kühne, Thomas; Loos, Katja; Devi, Anjana (Dalton Transactions)
The influence of different polymer side chains on the vapor phase infiltration with TMA is investigated and supported by DFT-calculations.
Keywords: Inorganic Chemistry

Impact of lunch with carbohydrates differing in glycemic index on children's cognitive functioning in the late postprandial phase: a randomized crossover study - Drozdowska, Alina; Sinningen, Kathrin; Falkenstein, Michael; Rudolf, Henrik; Libuda, Lars; Buyken, Anette; Lücke, Thomas; Kersting, Mathilde (European Journal of Nutrition)
Abstract Purpose Studies about effects of lunch dietary Glycemic Index (GI) on cognition of schoolchildren are scarce. Our previous CogniDo GI study found no changes of cognition in the early postprandial phase after consumption of two rice types with medium vs. high dietary GI for lunch (i.e., 45 min after starting lunch). This study investigated whether the dietary GI of lunch has an impact on cognition of schoolchildren in the late postprandial phase, 90 min after lunch. Methods A randomized, 2 × 2 crossover intervention study was conducted at a comprehensive school with 5th and 6th grade students. Participants ( n = 212) were randomly assigned to either sequence 1 or 2. In the first period, participants of sequence 1 received a dish with high GI rice (GI: 79), those of sequence 2 with medium GI rice (GI: 64)—in the second period, 1 week later, vice versa. Computer-based cognitive testing was performed 90 min after lunch examining tonic alertness, visual search and task switching, and working memory. Treatment effects and treatment effects adjusted for estimated lunch glycemic load (GL) were analyzed using a linear mixed model. Results The selected cognitive parameters were not affected by the GI of lunch 90 min after lunch, neither after intention-to-treat nor in the per-protocol analysis. Adjustment for GL also did not change results. Conclusion The present study revealed no notable differences after the consumption of two rice types with medium vs. high dietary GI for lunch in children’s cognitive function in the late postprandial phase, 90 min after lunch. Clinical trial registration German Clinical Trials Register (DRKS00013597); date of registration: 16/04/2018, retrospectively registered.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Das Praxissemester aus der Perspektive von Mentor*innen: Aufgaben der Lernorte und wahrgenommene Veränderungsbedarfe - Caruso, Carina; Goller, Michael (Lehrerbildung auf dem Prüfstand)
Mentor*innen unterstützen Studierende u.a. bei der Planung, Durchführung und Reflexion von Unterricht. Obwohl Mentor*innen ein hoher Einfluss auf die Professionalisierung angehender Lehrkräfte zugeschrieben wird, gibt es nur wenige Studien, in denen die Perspektive von Mentor*innen beforscht wird. Dieser Beitrag zielt darauf, die Perspektive von Mentor*innen zu den Aufgaben der am Praxissemester beteiligten Lernorte sowie Veränderungsbedarfe zu explorieren. Hierzu werden Ergebnisse einer Interviewstudie mit 23 Mentor*innen vorgestellt, die zur Beantwortung nachstehender Forschungsfragen beitragen: (1) Welche Aufgaben haben die am Praxissemester beteiligten Lernorte und die dort tätigen Akteur*innen hinsichtlich der Vorbereitung, Unterstützung und Begleitung der Studierenden im Praxissemester aus Perspektive befragter Mentor*innen? (2) Was sind aus Sicht von Mentor*innen Veränderungsbedarfe hinsichtlich der Rahmenbedingungen bzw. Konzeption des Praxissemesters? Ein zentraler Befund der Studie ist, dass allen Lernorten attribuiert wird, dass diese Studierende auf die praktische Unterrichtstätigkeit vorbereiten sollen. Die Relevanz der Universitäten wird dabei allerdings als gering eingeschätzt. Auch theoretisch-reflexive Aspekte spielen in den Aussagen der meisten Mentor*innen keine Rolle. Veränderungsbedarf wird von den Mentor*innen vor allem in der Rolle des Zentrums für schulpraktische Lehrerausbildung und der Universität gesehen. Diese Befunde werden anschließend kritisch diskutiert.
Keywords: Lehrerbildung; Mentoring; Praxissemester; Professionalisierung / internship; mentoring; professionalisation; teacher education

Aufgaben, Ziele und Betreuungsstrategien von am Praxissemester beteiligten Lehrkräften - Caruso, Carina; Goller, Michael (PraxisForschungLehrer*innenBildung)
Im Praxissemester sind Mentor*innen für Studierende wichtige Bezugspersonen und Kooperationspartner*innen, die die Studierenden u.a. bei der Planung, Durchführung und Reflexion von Unterricht begleiten. Während z.B. zur Kompetenzentwicklung Studierender im Praxissemester mehrere Erkenntnisse vorliegen, wurde die Perspektive von Mentor*innen bisher wenig untersucht. Dieser Beitrag zielt darauf, die Perspektive und Erfahrungen von Mentor*innen zu explorieren und sichtbar zu machen. In diesem Zusammenhang werden Ergebnisse einer leitfadenzentrierten Interviewstudie vorgestellt, an der 23 nordrhein-westfälische Lehrkräfte teilnahmen. Auf Grundlage der inhaltsanalytischen Auswertung der Transkripte werden die nachstehenden Fragestellungen beantwortet: (1) Was sind aus Sicht von Mentor*innen Aufgaben im Zusammenhang mit der Betreuung und Begleitung von Praxissemesterstudierenden? (2) Welche Ziele haben Praxisphasen aus der Perspektive der Mentor*innen? (3) Welchen Betreuungsstrategien folgen Mentor*innen bei der Betreuung und Begleitung von Praxissemesterstudierenden? Die Ergebnisse zeigen, dass die Antworten der Mentor*innen hinsichtlich der ihnen selbst zugeschriebenen Aufgaben und der dem Praxissemester attribuierten Ziele kaum differieren. Die Betreuungsstrategien der Befragten unterscheiden sich hingegen vergleichsweise stark. Unterschiede bestehen u.a. bezüglich der den Studierenden zugesprochenen Freiheitsgrade bei der Unterrichtsplanung und -durchführung sowie bei der (gemeinsamen) Gestaltung der Unterrichtsplanung bzw. -vorbesprechung.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Kompetenzentwicklung